INTERPRETATION OF PERSONALITY PROBLEMS IN ZIGMUND FREUD'S VIEWS (TAMADDUN NURI JURNALI, 2024)
This article reveals the essence of the views of S.Freud, the founder of psychoanalysis, the ability to correctly apply psychological methods in the client-psychologist-psychotherapist relationship, as well as the knowledge underlying any problem, pathology, disease in the process. Psychological consultation creates a theoretical basis for identifying and eliminating this or that psychological trauma.